PEMANFAATAN CABANG DENGAN KULIT KAYU SENGON (PARASERIANTHES FALCATARIA L. NIELSEN) SEBAGAI BAHAN BAKU PULP DALAM UPAYA MENGURANGI KERUSAKAN HUTAN - Ridwan Yahya (Environmental Research Center (PPLH) of Udayana University, 2010)
Based on preliminary researches, stem and branchwood of Paraserianthes falcataria L. Nielsen were suitable as raw material for pulp and paper manufacture. For the whole tree the highest proportion of bark was found in branches and the top of the tree with a value ranging 20 – 35%. Up to now, the pulp industries have spent money to remove bark of P. falcataria branch before pulping. The objective of this study was to know the suitability of branches including bark as raw material for pulp and paper manufacture. Samples were determined for fiber dimension and its derivation. Screened chips were cooked with the Kraft process. Liquor-to-wood-ratio was 4 : 1. Chemical charge was 13.3% NaOH and 6.7% Na2S. The temperature was raised from room temperature to 170 oC for 90 min and kept at this temperature for 90 min. Pulp was washed; then kappa number, screened and rejected pulp, residual of black liquor were determined. Research results showed that pulp branchwood with bark has the values of screened pulp yield, alkali consumption, and kappa number 46.91%; 9,57; and 25.63, respectively. It paper product has the values of breaking length, burst factor, stretch, tensile strength, and opacity 9.94; 83.80; 3.57%; 1,733.34; 6.33 kN/m, and 92.85%, respectively. Based on those results, paper from branchwood with bark meets requirement for book, mimeograph, and photocopy papers.